Taxonomic revision of the subfamily Cladonotinae (Orthoptera: Tetrigidae) from China with description of three new species - Deng, Wei-An (Zootaxa, 2020)
The Chinese genera and species of the subfamily Cladonotinae are reviewed. A checklist is given for all genera and species. Three new species are described from China: Pseudepitettix hainanensis sp. nov. (Hainan prov.), Pseudepitettix strictivertex sp. nov. (Hainan prov.) and Tuberfemurus convexa sp. nov. (Zhejiang prov.). New synonymies are proposed: Deltonotus hainanensis Zheng & Liang, 1985 = Deltonotus wuzhishanensis Lin & Zheng, 2014, syn. nov., Gibbotettix emeiensis Zheng, 1992 = Gibbotettix serrifemura Deng, Zheng & Wei, 2016, syn. nov., Gibbotettix emeiensis Zheng, 1992 = Gibbotettix longivalva Zha & Li, 2018, syn. nov., Pseudepitettix nigritibis Zheng & Jiang, 2000 = Tuberfemurus liboensis Deng, Zheng & Wei, 2009, syn. nov., Yunnantettix bannaensis Zheng, 1995 = Yunnantettix variabilis Zha & Wen, 2016, syn. nov., Yunnantettix thaicus Storozhenko & Pushkar, 2015 = Yunnantettix nanensis Zha & Wen, 2015, syn. nov. Four new combinations are established: Epitettix guangxiensis (Zheng & Jiang, 1994), comb. nov., Epitettix yunnanensis (Zheng, 1995), comb. nov., Gibbotettix undatimarginis (Deng & Zheng, 2012), comb. nov., Pseudepitettix torulosinota (Zheng & Lin, 2016), comb. nov.